Assets Originating from Crimes Committed Abroad Within the Scope of Article 282 of the TPC: A Comparative Study on the Rule of Dual Criminality - Mustafa Akgün (Ceza Hukuku ve Kriminoloji Dergisi)
Article 282, paragraphs 1 and 2, of Turkish Penal Code No. 5237, establish two separate offenses concerning assets originating from a crime that requires a minimum sentence of six months or more imprisonment. This paper presents two separate arguments regarding assets derived from a crime committed abroad. First, it has been shown that assets originating from a crime committed abroad can be subject to Article 282 of Law No. 5237 without requiring the condition of dual criminality and that the counterargument based on the principle of legality and legal certainty, as well as the claim based on Article 6(2)(c) of the Palermo Convention, is not acceptable. Second, the risks of applying the principle of dual criminality in the predicate offense, within the context of the said crime, in all or nothing fashion, either universally or not at all, have been explained, and the appropriateness of the narrowed dual criminality rule, which has been accepted in the United Kingdom and Germany and is also reflected in the European Union regulations, has been demonstrated, as well as the need for legal changes to achieve this.